THE IMPACT OF BANK HEALTH ON EARNINGS MANAGEMENT IN STATE-OWNED BANKS IN INDONESIA - Natasya Irene Kaligis; Frisky Jeremy Kasingku (SEAN Institute, 2022)
This study empirically examines the effect of bank health as measured by Risk Profile, Good Corporate Governance, Earnings, and Capital on earnings management in state-owned banks in Indonesia. This study uses secondary data from financial reports from 2013-2020 with a total of thirty-two observations. This study uses multiple regression analysis with panel data. Panel data regression analysis technique is used with the dependent variable of earnings management measured using discretionary accruals and six independent variables to measure bank health: non-performing loans, loan-to-deposit ratio, good corporate governance, return on assets, net interest margin, and capital adequacy ratio. The result of the study shows that partially, non-performing loans, good corporate governance, return on assets, net interest margin, and capital adequacy ratios have no significant effect on earnings management. However, bank health simultaneously affects earnings management. On the other hand, partially, the loan-to-deposit ratio has a significant effect on earnings management. The findings in this study indicate that the higher the loan-to-deposit ratio reflects, the higher the bank's income which motivates management to conduct earnings management. Thus, regulations must be maintained for the banks to maintain and improve the bank's health.